(untitled) (Praxis Educativa, 2018)
The manifesto for education was, at the time, an attempt to answer a number of issues that concern education. After some years of its publication we return to its foundations and reflect on them in the light of current concerns. In these lines we revisit the manifesto knowing that many of the aims and objectives of that publication are present today and invite us to continue the struggle.